CHALLENGING PATRIARCHY IN PARADISE: MARK TWAIN'S PROGRESSIVE GENDER PORTRAYAL IN 'DIARIES OF ADAM AND EVE’ - Ali, Muhammad Ilham (English Education Department of STKIP Pasundan, 2024)
Despite extensive research on Mark Twain's works, few studies have examined his portrayal of gender roles in